1988
DOI: 10.1083/jcb.106.4.1161
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular targeting of isoproteins in muscle cytoarchitecture.

Abstract: Abstract. Part of the muscle creatine kinase (MM-CK) in skeletal muscle of chicken is localized in the M-band of myofibrils, while chicken heart cells containing myofibrils and BB-CK, but not expressing MM-CK, do not show this association. The specificity of the MM-CK interaction was tested using cultured chicken heart cells as "living test tubes" by microinjection of in vitro generated MM-CK and hybrid M-CK/B-CK mRNA with SP6 RNA polymerase. The resulting translation products were detected in injected cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Interestingly, attempts to reproduce the sorting of endogenous proteins by introducing labeled proteins, e.g., a-actinins of different sources, into cultured cells (McKenna et al, 1985;Sanger et al, 1986) have hitherto failed. Success was reported, however, by Schafer and Perriard (1988), who showed by microinjecting synthetic RNAs coding for two isoforms of creatine kinase (B-CK and M-CK) and chimeras thereof that the M-CK targeting to the myofibrillar M line appeared to be directed by isoform-specific characteristics embedded mainly in the C-terminal half of the M-CK isoprotein structure. We report in this article, using transfection and microinjection of epitope-tagged LC constructs, that the essential LC is subjected to a precise intracompartmental isoprotein-specific sorting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, attempts to reproduce the sorting of endogenous proteins by introducing labeled proteins, e.g., a-actinins of different sources, into cultured cells (McKenna et al, 1985;Sanger et al, 1986) have hitherto failed. Success was reported, however, by Schafer and Perriard (1988), who showed by microinjecting synthetic RNAs coding for two isoforms of creatine kinase (B-CK and M-CK) and chimeras thereof that the M-CK targeting to the myofibrillar M line appeared to be directed by isoform-specific characteristics embedded mainly in the C-terminal half of the M-CK isoprotein structure. We report in this article, using transfection and microinjection of epitope-tagged LC constructs, that the essential LC is subjected to a precise intracompartmental isoprotein-specific sorting.…”
Section: Discussionmentioning
confidence: 99%
“…The protein under study from one species has to be introduced into a cellular background devoid of homologous proteins with immune cross-reactivity. This technique allows researchers to follow proteins introduced in the form of a biochemically purified protein, as a synthetic RNA transcribed from full-length cDNA (Schafer and Perriard, 1988), or as cDNA cloned in a eukaryotic expression vector (Bendori et al, 1989;Friedrich et al, 1989;Ngai et al, 1990). The main limitation of this technique is the difficulty of raising antibodies with the necessary specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly there is sequence divergence between MM and BB-CK in the carboxyl-terminal of the enzyme. By expressing M-CK/B-CK fusions it has been shown that the carboxyl terminus of M-CK contains the information necessary for localization to myofibrils (41). In addition, differences in nontranslated regions of CK mRNA have been shown to cause localization of M-CK transcripts to myofibrils and control mRNA stability in B-CK transcripts (42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, untreated lysates had to be used for cotranslational phosphorylation and incorporation of 32P yielded only very faint signals due to the high endogenous phosphate pools. Incubation was followed by immunoprecipitation [23,27] and extensive washing before preparation of the samples for 2D gel analysis.…”
Section: Cotranslational Phosphotylation Assaysmentioning
confidence: 99%
“…An additional species termed Bb* was also isolated, although its nature remained unresolved [20]. Some minor species identified in cDNA-derived in vitro translation products [22,23], termed Bbl, Bb2 and Bb3 [24], are shown here to be phosphoproteins, which comigrate with Bb*.…”
Section: Introductionmentioning
confidence: 99%